Using Project Work to Help Students Understand How Individual Roles Benefit Cooperative Learning (2016)
ABSTRACT: This action research study was conducted in order to raise students’ awareness about how individual roles benefit cooperative learning. The data collection instruments used were: a teacher journal, two writing tasks and a peer and self-assessment. The studyrevealed that students’ commitment in the activities as well as the awareness about the importance in group working increased considerably through project work.